Examining the Role of Informational Justice in the Wake of Downsizing from an Organizational Relationship Management Perspective - Kim, Hyo-Sook (Journal of business ethics, 2008)
The purpose of this study was to examine how employees’ experiences, in the wake of an organization’s downsizing, would influence employee–organization relationships and the employees’ decisions to remain with the organization. In investigating survivors’ responses to downsizing, informational justice was chosen as an antecedent of the survivors’ intentions to leave and Organization–Public Relationship (OPR) was hypothesized to function as a mediator between informational justice and turnover intentions. The results revealed significant associations between informational justice and OPR as well as associations between OPR and turnover intentions in a downsizing context. Also, it was shown that OPR mediates the relationship between informational justice perceptions during the downsizing and turnover intentions after the downsizing.